A systematic review: How to implementation of problem solving model in chemistry learning? - Ayar Sakinah; Sri Handayani (Pascasarjana Universitas Negeri Medan, 2024)
Chemistry is one of the difficult subjects at all levels of education, this is what makes it difficult for students to solve problems so that student learning outcomes decrease. The things that cause chemistry learning problems are influenced by monotonous learning process activities, the application of less innovative learning models and methods that have a negative impact on students' ability to understand chemical concepts. This research aims to find out the implementation of problem solving in chemistry learning. This research method uses a systematic literature review (SLR) by analyzing previous research using the Google Scholar and Scopus databases in the last 10 years, namely 2014-2022. The 14 articles reviewed were obtained after going through the scanning process according to the inclusion criteria. The results of this study indicate that in chemistry learning it is necessary to improve problem solving in chemistry learning.